Speaking and Thinking A Conversation with Victor Ferreira. - Burton, Howard (Ideas Roadshow Conversations Ser., 2020)
This book is based on an in-depth filmed conversation between Howard Burton and Victor Ferreira, Professor of Psychology and Principal Investigator at the Language Production Lab at the University of California at San Diego. This extensive conversation explores Victor Ferreira's research which is focused on language production and communication, especially with regard to grammar, lexical structure and speaker-hearer interaction, and his interests to incorporate computational and quantitative modelling of cognitive processing. Topics under discussion include key experimental results that change.